PENGGUNAAN TEKNOLOGI INFORMASI DALAM PENDIDIKAN - Fenny Purwani (Wardah, 2013)
The development of information communication technology (ICT) or Information and Communication Technology (ICT) is increasingly more active over the last two decades and has created a change in many ways, including in education. Information technology is a combination of computer technology, databases, networks and improved communications, and Information Management Personnel. The aplication of ICT in teaching and learning can be use to make learning media (CAI), e-Learning, Virtual Library, the Virtual School and the Virtual University